2020
DOI: 10.1177/1075547020932174
|View full text |Cite
|
Sign up to set email alerts
|

How 360-Degree Video Influences Content Perceptions and Environmental Behavior: The Moderating Effect of Environmental Self-Efficacy

Abstract: Whereas the positive impact of 360-degree video on user experience has been demonstrated, its persuasive potentials have not been fully investigated. A lab experiment compared proenvironmental 360-degree videos and unidirectional videos in their persuasive effectiveness. Environmental self-efficacy, the degree to which individuals believe that they can influence the outcomes associated with global warming, has been proposed as a moderator. In a lab experiment ( N = 76), higher environmental self-efficacy parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 65 publications
2
17
0
Order By: Relevance
“…Thus some ambiguity exists about whether to examine environmental behaviors at an individual and/or societal level. Many studies use measures that combine different aspects of PEBs (e.g., Abraham et al, 2015; Axelrod & Lehmen, 1993; Berger & Corbin, 1992; Chen, 2015; Heeren et al, 2016; Homburg & Stolberg, 2006; Huang, 2016; Lee & Holden, 1999; Lee et al, 2014; Oh et al, 2020; Oreg & Katz-Gerro, 2006; Rice et al, 1996; Wu & Mweemba, 2010). For example, some distinguish between activist and non-activist behaviors (Chen, 2015; Homburg & Stolberg, 2006; Piyapong, 2020) as PEBs.…”
Section: Pro-environmental Behaviorsmentioning
confidence: 99%
“…Thus some ambiguity exists about whether to examine environmental behaviors at an individual and/or societal level. Many studies use measures that combine different aspects of PEBs (e.g., Abraham et al, 2015; Axelrod & Lehmen, 1993; Berger & Corbin, 1992; Chen, 2015; Heeren et al, 2016; Homburg & Stolberg, 2006; Huang, 2016; Lee & Holden, 1999; Lee et al, 2014; Oh et al, 2020; Oreg & Katz-Gerro, 2006; Rice et al, 1996; Wu & Mweemba, 2010). For example, some distinguish between activist and non-activist behaviors (Chen, 2015; Homburg & Stolberg, 2006; Piyapong, 2020) as PEBs.…”
Section: Pro-environmental Behaviorsmentioning
confidence: 99%
“…For example, Horning (2017) examined the impact of second screen interactions on viewers' perceived enjoyment of news content. Oh et al (2020) demonstrated that 360-degree videos had a greater indirect effect on the positive emotions evoked by video content, through enhanced perceived interactivity, than did 2D videos. Recent automatic facial expression detection-based studies measuring emotions evoked by ads have demonstrated that interactive advertising elicits positive emotions (e.g., Teixeira et al, 2012;Lewinski et al, 2014;Castellanos et al, 2018;Lacroix et al, 2020).…”
Section: Effects Of Interactivity On Affective Processing: Emotions E...mentioning
confidence: 91%
“…Therefore, the efficacy of 360-degree video ads should be examined (Feng, 2018). Surprisingly, despite the growth in the use of 360-degree videos, and their distinctive features, there has been little academic research into their effectiveness in advertising; and the scarce research that has been undertaken has used self-reported measures of consumers' responses (Feng et al, 2019;Oh et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…When citizens have more confidence in their ability to complete tasks, their self-efficacy may be increased. Thus, Oh et al (2020) suggest that citizens' self-understanding of science issues will relate positively to scientific self-efficacy. Additionally, it is hypothesized that scientific interest and self-understanding may be related to science learning enjoyment and scientific self-efficacy (Lin et al, 2013a).…”
Section: Introductionmentioning
confidence: 99%